2017
DOI: 10.1037/dev0000308
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of neighborhood collective efficacy and maternal corporal punishment with behavior problems in early childhood.

Abstract: Neighborhood and parenting influences on early behavioral outcomes are strongly dependent upon a child's stage of development. However, little research has jointly considered the longitudinal associations of neighborhood and parenting processes with behavior problems in early childhood. To address this limitation, this study explores the associations of neighborhood collective efficacy and maternal corporal punishment with the longitudinal patterns of early externalizing and internalizing behavior problems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 66 publications
2
44
1
Order By: Relevance
“…Our findings were consistent with numerous prior studies of the FFCWS, in that we found the associations of maternal spanking with elevated levels of both externalizing and internalizing child behavior problems (Ma & Grogan‐Kaylor, 2017; Maguire‐Jack et al, 2012; Taylor, Manganello, Lee, & Rice, 2010). Also consistent with a prior FFCWS study that used fixed effects analysis, we found that community violence predicted higher levels of child aggression (Ma et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were consistent with numerous prior studies of the FFCWS, in that we found the associations of maternal spanking with elevated levels of both externalizing and internalizing child behavior problems (Ma & Grogan‐Kaylor, 2017; Maguire‐Jack et al, 2012; Taylor, Manganello, Lee, & Rice, 2010). Also consistent with a prior FFCWS study that used fixed effects analysis, we found that community violence predicted higher levels of child aggression (Ma et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The education literature has also devoted considerable attention to collective efficacy and found a close link between the belief of teachers in the collective efficacy of their school and student achievement (Goddard 2002(Goddard , 2001Goddard, Hoy, and Hoy 2000;Bandura 1993). Collective efficacy is relevant in a wide range of contexts, including pro-environmental behaviour (Chen 2015), group problem solving (Kline and MacLeod 1997), substance abuse (Fagan, Wright, and Pinchevsky 2014), athletics (Greenlees, Graydon, and Maynard 1999), child development (Smith et al 2013), parenting (Ma and Grogan-Kaylor 2017), political attitude and participation (Lee 2006) and community gardening (Teig et al 2009).…”
Section: Effects Of Collective Efficacymentioning
confidence: 99%
“…Collective efficacy is defined as the connections and social relationships among community members combined with the willingness to utilize these relationships to facilitate community change (Odgers et al., ). Recent research focuses on the relationships between collective efficacy at the neighborhood level (i.e., neighborhood collective efficacy) and a wide range of topics including intimate partner violence (Jackson, ), fear of crime among public housing residents (Kilewer, ), neighborhood crime and violence (Browning, Feinberg, & Dietz, ; Higgins & Hunt, ; Hipp, ; Pegram, Brunson, & Braga, ), adolescent substance abuse (Fagan, Wright, & Pinchevsky, ; Jackson, Denny, Sheridan, Zhao, & Ameratunga, ), child development (Smith, Osgood, Caldwell, Hynes, & Perkins, ), parenting (Ma, ; Ma & Grogan‐Kaylor, ; Zuberi, ), and community gardening (Teig et al. ().…”
Section: Introductionmentioning
confidence: 99%
“…, child development (Smith, Osgood, Caldwell, Hynes, & Perkins, 2013), parenting (Ma, 2016;Ma & Grogan-Kaylor, 2017;Zuberi, 2016), and community gardening (Teig et al (2009).…”
mentioning
confidence: 99%